2001
DOI: 10.1136/bjsm.35.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in whitewater kayaking

Abstract: Objective-To provide epidemiological data on whitewater kayaking injuries using a descriptive study. Methods-A retrospective survey was distributed at whitewater events and club meetings, and made available and advertised on the world wide web, through postings and announcements to newsgroups, related sites, and search engines. Data on sex, age, experience, and ability were collected. Injury data collected included mechanism, activity, diYculty of rapid, and self reported severity. Results-Of the 392 kayaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 17 publications
5
65
0
1
Order By: Relevance
“…Various methods of data collection were reported. Surveys were used in seven studies [10,[12][13][14][16][17][18], provider records were used in three studies [19][20][21], hospital discharge data were used in a further two studies [22,23], and observation [11], telephone interview [15], tourist compensation claim data [24] and kinematic data [25] were identified in single articles. Samples ranged between 54 and 473 participants of which between 53.5% and 89% were male.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Various methods of data collection were reported. Surveys were used in seven studies [10,[12][13][14][16][17][18], provider records were used in three studies [19][20][21], hospital discharge data were used in a further two studies [22,23], and observation [11], telephone interview [15], tourist compensation claim data [24] and kinematic data [25] were identified in single articles. Samples ranged between 54 and 473 participants of which between 53.5% and 89% were male.…”
Section: Resultsmentioning
confidence: 99%
“…Fiore and Houston [16], reported that novices, defined as those competent on grade I and II rivers, sustain more acute impact-related injuries, such as abrasions, lacerations, sprains, strains and fractures. Expert paddlers, on the other hand, defined as individuals who are competent on grade V and VI rivers, sustain more chronic overuse injuries, such as tendonitis [16]. Acute and chronic injuries and injury rates have been examined in WW paddling and rafting separately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations